An Ideological Construction Disseminated in Persuading People Used by Dr. Joe in Paper Writing Training of His Rumah Scopus. - Saputro, Suswanto Ismadi Megah; Artanto, Tri; Handayani, Pristika; Anugrah, Rizki Tri (eScience Humanity Journal, 2024)
This paper deals with ideology disseminated of the language styles used by Dr. Joe, the president of ‘Rumah Scopus”. This paper has an objective to open his ideological power of persuasion behind his words to influence many people. This study applied language style theory of Keraf. The findings shows that there are four techniques used by Dr. Joe in conveying his training. Such as suggestion techniques, compensation techniques, rationalization techniques and identification techniques. Of the four techniques, there were 5 excepts, and there were three language styles used by Dr. Joe are hyperbole, personification, simile, repetition and Metonimia. Hence, the most dominant is the suggestion technique is meant that Dr, Joe tends to persuade the training participants. This is the ideology used by Dr. Joe in strengthening the trust of many people for training at his place, namely Scopus House. Based on the description above, the following two things can be concluded. First, the persuasion techniques produced in Dr. Joe provides excellent explanations so that the training participants will be amazed to follow and deepen their science and knowledge. So that participants have good courage to write in reputable international journals, especially Scopus. Because with this journal, participants can continue their higher educational careers. Thus, the main point of this study the power of lexical choice is the great weapon to convince the participants to join in his writing training camp. Keywords: Ideological construction Persuading Paper Writing Training